PENDIDIKAN KEMANDIRIAN MELALUI KEGIATAN EKONOMI DI PONDOK PESANTREN PERSPEKTIF PENDIDIKAN ISLAM - Misjaya, Misjaya (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2022)
Muslims as the majority of Indonesian people, there are still many who are below the poverty line. When the number of unemployed in 2010 was recorded at 41.395 million, the largest number of unemployed was Muslims. Islamic boarding schools have been known for their independence, especially in terms of the economy. Kiai as managers as well as teaching staff in Islamic boarding schools are the main key to the success of independent education for students. This study aims to find an independent education system through economic activities in an ideal Islamic boarding school from the perspective of Islamic education. The research method uses a qualitative approach with a library research pattern and content analysis techniques. The conclusion of this research is that the spirit of independence of the students through economic activities must be internalized and animate every behavior of the students. The spirit of independence will have a positive influence on the aqidah, worship, etiquette, and social life of the students at large. In the case of aqidah, for example, the most profitable offer is to purify aqidah and stay away from shirk, because the biggest benefit is heaven. In economic activities, the students will choose business ethics that are in accordance with Islamic sharia from others, because the guarantee of big profits is in carrying out Islamic law. In addition to material benefits, you will also get non-material benefits in the form of muamalah piety and worship piety at the same time.Keywords: Education, independence, economy, Islamic boarding school